2016
DOI: 10.1038/ijos.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

One-year water-ageing of calcium phosphate composite containing nano-silver and quaternary ammonium to inhibit biofilms

Abstract: Dental composites are commonly used restorative materials; however, secondary caries due to biofilm acids remains a major problem. The objectives of this study were (1) to develop a composite containing quaternary ammonium dimethacrylate (QADM), nanoparticles of silver (NAg), and nanoparticles of amorphous calcium phosphate (NACP), and (2) to conduct the first investigation of the mechanical properties, biofilm response and acid production vs water-ageing time from 1 day to 12 months. A 4 × 5 design was utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 56 publications
1
68
0
2
Order By: Relevance
“…Hence, in accordance with those previous studies [110,111], we have chosen 5.5 wt% of AgNP, to vet any possible detrimental effects of the nanoparticles on penetration ability of the infiltrant resin. It is known that, next to the long-term bactericidal activity and the decreased lactic acid production driven by the nanosilver [50,112,113], AgNP increased the surface hydrophobicity of composite resins, even with low mass fractions of down to 0.3 wt% [114]. Additionally, it is worth mentioning that with these low concentrations, mechanical characteristics (like flexural strength, or elastic modulus) of the composites matched those of commercial products [112,113], even though some reports have indicated an influence on polymerization, thus increasing the amount of elutable monomers [115].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in accordance with those previous studies [110,111], we have chosen 5.5 wt% of AgNP, to vet any possible detrimental effects of the nanoparticles on penetration ability of the infiltrant resin. It is known that, next to the long-term bactericidal activity and the decreased lactic acid production driven by the nanosilver [50,112,113], AgNP increased the surface hydrophobicity of composite resins, even with low mass fractions of down to 0.3 wt% [114]. Additionally, it is worth mentioning that with these low concentrations, mechanical characteristics (like flexural strength, or elastic modulus) of the composites matched those of commercial products [112,113], even though some reports have indicated an influence on polymerization, thus increasing the amount of elutable monomers [115].…”
Section: Discussionmentioning
confidence: 99%
“…One possible prospective filler candidate would seem silver nanoparticles (AgNP) [43], ranging from 1 to 100 nm in diameter; in recent years, AgNP have been increasingly used for a wide range of applications in (nano-)medicine, and successful dental implementations have been reported as well [44,45], including composite resins [46,47]. The desired antimicrobial effects have been revealed [48,49], and especially the long-lasting [50] and the long-distance bactericidal capability [51] should qualify AgNP as complimentary additives to infiltrant resins, thus preventing the latter from microbial re-colonization.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse research with different additives has been carried out to develop effective antibacterial resin-based composites. Most of these additives are organic bactericides, such as: quaternary ammonium dimethacrylate (QADM) [21], dimethylaminohexadecyl methacrylates (DMAHDM) [22], dimethyl-hexadecylmethacryloxyethyl-ammonium iodide (DHMAI) [23], quaternary ammonium polyethylenimine (PEI) nanoparticles [24], chlorhexidine [25], triclosan [26] or chitosan [27]. Inorganic coatings have emerged as an alternative approach since they present several advantages compared to traditional organic agents, which include chemical stability, thermal resistance and protracted action, and they have not yet been associated with resistant organisms [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some cells on NACP-QADM nanocomposites have been shown to disintegrate [98]. In addition to QAMs, it has been shown that the antimicrobial activity of ACP (amorphous calcium phosphate) and CaF2 nanocomposites can be greatly increased when added to CHX fillers, while the ability of biofilm formation was significantly reduced [98][99][100].…”
Section: Antimicrobial Agents With Remineralizingmentioning
confidence: 99%